Peran Guru dalam Membentuk Karakter Disiplin Belajar pada Murid Melalui Kegiatan Belajar Tambahan di Sekolah Dasar Yayasan IBA Palembang - Izzatul Jannah; Al Ihwanah; Ines Tasya Jadidah; Faisal; Agra Dwi Saputra (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Learning discipline is one of the important characters that needs to be developed from the elementary school level so that students possess responsibility and orderliness in the learning process. However, in reality, some students have not demonstrated optimal learning discipline; therefore, the role of teachers is needed through additional learning activities. This study aims to analyze the implementation of additional learning activities, the role of teachers in shaping students’ learning discipline, and the factors influencing it at SD Yayasan IBA Palembang. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of teachers, third-grade students, and the school principal. Data were collected through observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was tested using source triangulation and technique triangulation. The results showed that additional learning activities were implemented through three aspects: planning, interaction and supervision, and learning evaluation. The teachers’ roles in these activities included acting as educators, demonstrators, classroom managers, motivators, and evaluators. Supporting factors included students’ self-awareness, school support, and parental support, while inhibiting factors included limited implementation time and the lack of parental assistance at home. Based on the findings, it can be concluded that the consistent and integrated optimization of teachers’ roles in additional learning activities is the main factor in shaping and improving students’ learning discipline in elementary schools.